Rational Targeting of Cdc42 Overcomes Drug Resistance of Multiple Myeloma - Nguyen, Phuong; Chakrabarti, Jayati; Li, Yuan; Kalim, Khalid W.; Zhang, Mengnan; Zhang, Lin; Zheng, Yi; Guo, Fukun (Frontiers in Oncology, 2019)
Multiple myeloma (MM) drug resistance highlights a need for alternative therapeutic strategies. In this study, we show that CASIN, a selective inhibitor of cell division cycle 42 (Cdc42) GTPase, inhibited proliferation and survival of melphalan/bortezomib-resistant MM cells more profoundly than that of the sensitive cells. Furthermore, CASIN was more potent than melphalan/bortezomib in inhibiting melphalan/bortezomib-resistant cells. In addition, CASIN sensitized melphalan/bortezomib-resistant cells to this drug combination. Mechanistically, Cdc42 activity was higher in melphalan/bortezomib-resistant cells than that in the sensitive cells. CASIN inhibited mono-ubiquitination of Fanconi anemia (FA) complementation group D2 (FANCD2) of the FA DNA damage repair pathway in melphalan-resistant but not melphalan-sensitive cells, thereby sensitizing melphalan-resistant cells to DNA damage. CASIN suppressed epidermal growth factor receptor (EGFR), signal transducer and activator of transcription 3 (STAT3), and extracellular signal-regulated kinase (ERK) activities to a larger extent in bortezomib-resistant than in melphalan-sensitive cells. Reconstitution of ERK activity partially protected CASIN-treated bortezomib-resistant cells from death, suggesting that CASIN-induced killing is attributable to suppression of ERK. Importantly, CASIN extended the lifespan of mouse xenografts of bortezomib-resistant cells and caused apoptosis of myeloma cells from bortezomib-resistant MM patients. Finally, CASIN had negligible side effects on peripheral blood mononuclear cells (PBMC) from healthy human subjects and normal B cells. Our data provide a proof of concept demonstration that rational targeting of Cdc42 represents a promising approach to overcome MM drug resistance.